A Combined Effect of Self and Reward: Relationship of Self- and Reward-Bias on Associative Learning - Wang, Lingyun; Qi, Yuxin; Li, Lihong; Jia, Fanli (Frontiers in Psychology, 2021)
Previous studies have demonstrated that individuals process information related to themselves or a high reward quickly and have referred to this as self-bias or reward-bias. However, no previous study has presented self- and reward-bias simultaneously. The present study investigated perceptual processing using the associated learning paradigm when both self and reward were prioritized (condition of double salience) as well as when only self or reward was prioritized (condition of single salience). The present study established these two conditions by manipulating self-relevance (self vs. stranger in Experiment 1; self vs. friend in Experiment 2). The results showed that (1) when the self was pitted against a stranger and received a high or low reward, perceptual processing of the participants mainly involved self-bias (Experiment 1); (2) when the self was pitted against a friend, perceptual processing involved both self-bias and reward-bias (Experiment 2). The study revealed a complex relationship between self- and reward-bias, which depends on the degree of affinity between oneself and others.